Factors Affecting the Ups and Downs of Stock Prices in Food and Beverage Subsector Companies Listed on the IDX for the Period 2020-2022 - Shafa Fadilah Choirunnisah; Sintya Devi; Erwin Budianto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study analyzes the Return On Assets and Debt to Equity Ratio on the ups and downs of Stock Prices in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022. This study uses a purposive sampling method with 20 food and beverage sub-sector companies as samples. The variables used are ROA, DER, and Stock Price. This study uses a quantitative approach and data collection sourced from secondary data by collecting data on the financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) and other sources such as the official websites of related companies. The data analysis used is descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results shown in this study are (1) partial Return On Asset (ROA) has no significant effect on stock prices, (2) partial Debt Equity Ratio (DER) has no significant effect on stock prices, and (3) simultaneously Return On Asset (ROA) and Debt Equity Ratio (DER) have no significant effect on stock prices.